The Inhibitory Effect of α/β-Hydrolase Domain-Containing 6 (ABHD6) on the Surface Targeting of GluA2- and GluA3-Containing AMPA Receptors - Wei, Mengping; Jia, Moye; Zhang, Jian; Yu, Lulu; Zhao, Yunzhi; Chen, Yingqi; Ma, Yimeng; Zhang, Wei; Shi, Yun S.; Zhang, Chen (Frontiers in Molecular Neuroscience, 2017)
The α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-type glutamate receptors are major excitatory receptors that mediate fast neurotransmission in the mammalian brain. The surface expression of functional AMPA receptors (AMPARs) is crucial for synaptic transmission and plasticity. AMPAR auxiliary subunits control the biosynthesis, membrane trafficking, and synaptic targeting of AMPARs. Our previous report showed that α/β-hydrolase domain-containing 6 (ABHD6), an auxiliary subunit for AMPARs, suppresses the membrane delivery and function of GluA1-containing receptors in both heterologous cells and neurons. However, it remained unclear whether ABHD6 affects the membrane trafficking of Glutamate receptor subunits, GluA2 and GluA3. Here, we examine the effects of ABHD6 overexpression in HEK293T cells expressing GluA1, GluA2, GluA3, and stargazin, either alone or in combination. The results show that ABHD6 suppresses the glutamate-induced currents and the membrane expression of AMPARs when expressing GluA2 or GluA3 in the HEK293T cells. We generated a series of GluA2 and GluA3 C-terminal deletion constructs and confirm that the C-terminus of GluAs is required for ABHD6’s inhibitory effects on glutamate-induced currents and surface expression of GluAs. Meanwhile, our pull-down experiments reveal that ABHD6 binds to GluA1–3, and deletion of the C-terminal domain of GluAs abolishes this binding. These findings demonstrate that ABHD6 inhibits the AMPAR-mediated currents and its surface expression, independent of the type of AMPAR subunits, and this inhibitor’s effects are mediated through the binding with the GluAs C-terminal regions.